2008
DOI: 10.5713/ajas.2008.70581
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Inclusion of Palm Kernel Cake and Palm Oil, and Enzyme Supplementation on Performance of Laying Hens

Abstract: A total of 392 twenty eight week-old laying hens was used to study the effects of dietary inclusion of solvent-extracted palm kernel cake (PKC) (0%, 12.5% and 25%) and enzyme (mixture of mannanase, α-galactosidase and protease) supplementation (0 kg/t, 1 kg/t and 2 kg/t) on the performance of laying hens. The levels of PKC did not significantly influence nitrogen corrected true metabolizable energy (TME n ) of the diets. Enzyme-supplemented PKC had significantly higher AME and TME n values than PKC diets with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 22 publications
3
44
0
8
Order By: Relevance
“…It is well known that the yolk color is depended upon the characteristic of feed. In other study (Chong et al, 2008), PKM decreased the yolk color score with higher level (25%) of supplementation, but no influence with lesser level (12.5%) of supplementation. Therefore, substantially lower (5%) level of PKM supplementation in this study could be a reason why the same PKM did not induce change in yolk color score.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that the yolk color is depended upon the characteristic of feed. In other study (Chong et al, 2008), PKM decreased the yolk color score with higher level (25%) of supplementation, but no influence with lesser level (12.5%) of supplementation. Therefore, substantially lower (5%) level of PKM supplementation in this study could be a reason why the same PKM did not induce change in yolk color score.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is believed that the PKM inclusion contributed, in certain extent, for stimulating feed intake in this study. Several laying hen studies (Perez et al, 2000;Chong et al, 2008) reported increased feed intake by PKM inclusion in diets. However, there was a report (Zanu et al, 2012) which showed no difference in feed intake by dietary PKM inclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The colour of the egg yolk increased significantly (P < 0.05) (Afolabi et al 2012). Chong et al (2008) described the significantly lighter colour of the yolk when extracted palm kernel pomace was added in the feed for laying hens at an amount of 250 g•kg -1 . Supplementation of the feeding dose with 10-100 g•kg -1 linseed cake increased the level of thiocyanate in blood serum.…”
Section: Discussionmentioning
confidence: 99%
“…Also in previous studies, enzyme complex supplementation in palm kernel meal diets could improve growth performance in broilers (Chong et al, 2008) and pigs (Ao et al, 2011). Application of a carbohydrase cocktail to facilitate the breakdown of non-starch polysaccharides in 5% palm kernel meal diet could improve the growth performance and energy and nutrient digestibility in finishing pigs (Ao et al, 2011).…”
mentioning
confidence: 99%